How Germans prepare for the English past tense: Silent production of inflected words during EEG. (13th April 2015) - FESTMAN, JULIA; CLAHSEN, HARALD
ABSTRACT: Processes involved in late bilinguals' production of morphologically complex words were studied using an event-related brain potentials (ERP) paradigm in which EEGs were recorded during participants' silent productions of English past- and present-tense forms. Twenty-three advanced second language speakers of English (first language [L1] German) were compared to a control group of 19 L1 English speakers from an earlier study. We found a frontocentral negativity for regular relative to irregular past-tense forms (e.g., asked vs. held ) during (silent) production, and no difference for the present-tense condition (e.g., asks vs. holds ), replicating the ERP effect obtained for the L1 group. This ERP effect suggests that combinatorial processing is involved in producing regular past-tense forms, in both late bilinguals and L1 speakers. We also suggest that this paradigm is a useful tool for future studies of online language production.